2017
DOI: 10.17718/tojde.306554
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes Towards Edmodo, a Social Learning Network: A Scale Development Study

Abstract: Social Learning Networks (SLNs) are the developed forms of Social Network Sites (SNSs) adapted to educational environments, and they are used by quite a large population throughout the world. In addition, in related literature, there is no scale for the measurement of students' attitudes towards such sites. The purpose of this study was to develop a scale to determine students' attitudes towards Edmodo, a Social Learning Network (Edmodo Attitude Scale, EAS). The scale development process included reviewing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 11 publications
(10 reference statements)
5
17
0
3
Order By: Relevance
“…These outcomes supported the results of Alseweed (2009), Al- Shammari (2007), Thongmak (2013), Bahce and Taslaci (2009), Isiguzel (2014) Vernadakis, et al, (2012; Wesson et al, (2015). Similar to the findings of Bozanta and Mardikyan (2017), Tsiakyroudi (2018) and also Yunkul and Cankaya (2017), the students in this study believed that their self-esteem and writing motivation were increased as they could overcome writing difficulties by sharing ideas and giving feedbacks on each other's work easily.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These outcomes supported the results of Alseweed (2009), Al- Shammari (2007), Thongmak (2013), Bahce and Taslaci (2009), Isiguzel (2014) Vernadakis, et al, (2012; Wesson et al, (2015). Similar to the findings of Bozanta and Mardikyan (2017), Tsiakyroudi (2018) and also Yunkul and Cankaya (2017), the students in this study believed that their self-esteem and writing motivation were increased as they could overcome writing difficulties by sharing ideas and giving feedbacks on each other's work easily.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple studies have focused on university students' perceptions of Edmodo-enhanced instruction. The use of this new technology, has introduced an innovative scenario to the traditional instruction which resulted in positive perceptions towards Edmodo and MALL since it facilitates collaborative learning and students' self-confidence (Bozanta &Mardikyan, 2017;Yunkul & Cankaya, 2017). It also increases effectiveness of communication and language learning (Al-Said, 2015; Al- Shammari, 2007;Mokhta & Dzakiria, 2015;Sandu, 2015;Thongmak, 2013).…”
Section: Students' Perceptions Of Edmodomentioning
confidence: 99%
“…This study's results are in agreement with those of Yunkul and Cankaya (2017), who reported that students have positive attitudes toward Edmodo. This study's results are also in line with what Janpho, Chaeturat, and Multa (2015) found regarding the effectiveness of using social educational networking when teaching English.…”
Section: Students' Attitudes Toward Edmodosupporting
confidence: 92%
“…Social networking sites are popular as are cutting-edge communication products; such sites have dramatically changed the ways in which people and communities interact and exchange information. Social networking has spread across the world and has eliminated borders, thus allowing all people to both express their own views and access other people's ideas at any time and without conditions (Clark & Berge, 2006;Yunkul & Cankaya, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of relevant research studies on the relationship between TAM & IS model variables confirmed that service quality, information quality, system quality significantly influenced user satisfaction [19]; [7]; [2]; [21]. Perceived usefulness affects user satisfaction [9]; [21]; [22]; [11]. Perceived ease ouse gives influence to user satisfaction [9]; [17]; [2]; [11].…”
Section: User Acceptance and User Satisfaction Modelsmentioning
confidence: 94%